The role of judicial accounting in reducing tax evasion methods in Iraq - Dheyaa Zamil Khudhair, Ali Abdul Hussein Raji, Firas Abbas Al- Zubaidi, (Opción, 2019)
The study aims to investigate the role of judicial accounting in reducing tax evasion methods in Iraq via qualitative comparative methods. The article has reached several results that the most important of them is: there is a crucial need to apply judicial accounting in Iraq due to the widespread phenomenon of tax evasion in Iraqi companies. In conclusion, the judicial accountant must have many skills for the purpose of performing specialized functions including education and training in accounting, auditing, taxation and business.